2021
DOI: 10.1109/ted.2021.3067616
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of a Blocking Layer Structure for Low-Lag Operation of the a-PbO-Based X-Ray Detector

Abstract: Direct conversion flat panel detectors are of great significance to the field of medical X-ray imaging since they offer imaging performance and diagnostic capabilities not achievable with other methods. Currently, mammographic direct conversion detectors employ a layer of amorphous selenium (a-Se) photoconductor. Although its properties ideally fit the requirements of mammography, where "soft" X-rays are used, a-Se cannot be used in high-energy X-ray procedures. To extend the diagnostic capabilities of the dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…Generally speaking, the carriers can be trapped at localized states within the mobility gap of a-PbO, in either shallow or deep traps. However, a previous investigation of the ghosting effect [21] suggested that no deep trapping occurs in PI/a-PbO photoconductive structures, at least at the relatively low exposures used in this study. Ghosting is caused by deep bulk trapping of photogenerated carriers, which subsequently recombine with the drifting carriers of the opposite sign, resulting in sensitivity degradation.…”
Section: Introductionmentioning
confidence: 52%
See 4 more Smart Citations
“…Generally speaking, the carriers can be trapped at localized states within the mobility gap of a-PbO, in either shallow or deep traps. However, a previous investigation of the ghosting effect [21] suggested that no deep trapping occurs in PI/a-PbO photoconductive structures, at least at the relatively low exposures used in this study. Ghosting is caused by deep bulk trapping of photogenerated carriers, which subsequently recombine with the drifting carriers of the opposite sign, resulting in sensitivity degradation.…”
Section: Introductionmentioning
confidence: 52%
“…Finally, a top Au contact (readout electrode) 1.1 mm in diameter was sputtered atop of the a-PbO, which provided an effective detector area of 0.95 mm 2 . Detailed descriptions of the PI application and a-PbO deposition can be found in [21,56].…”
Section: Detector Preparationmentioning
confidence: 99%
See 3 more Smart Citations